Menggagas Fikih Tahkim Indonesia - Isa Ansori (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2021)
Fiqh is a legal product as a result of Mujtahid's thinking and understanding againts a particular legal case. The fiqh will continuesly develop along with the changes in place and time. Fikihtahkim is compiled by the ulama as a procedure for resolving conflicts outside the court. Some provisions of classical tahkim jurisprudence such as an arbitrator must be Muslim, it cannot be an infidel, a slave, an infidel zimmi, a person subject to qazaf, and wicked people, or an arbitrator must be in the same mazhab with the people or parties whose conflicts are being resolved, it could be not appropriate if applied in Indonesia, because the provisions like this are not generally carried out in the tradition of arbitration in Indonesia, so they require adjustments. These facts require Islamic jurists in Indonesia to reformulate the fiqhtahkim that consider the situation, conditions and culture of the Indonesian people. It should consider the practices of traditional arbitration wich has become as culture in society.